2020
DOI: 10.1093/mnras/staa003
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of bimodality in nebular phase Type Ia supernova spectra

Abstract: One observational prediction for Type Ia supernova (SNe Ia) explosions produced through white dwarf-white dwarf collisions is the presence of bimodal velocity distributions for the 56 Ni decay products, although this signature can also be produced by an off-center ignition in a delayed detonation explosion. These bimodal velocity distributions can manifest as double-peaked or flat-topped spectral features in latetime spectroscopic observations for favorable viewing angles. We present nebular-phase spectroscopi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 153 publications
0
13
1
Order By: Relevance
“…Some explosion models can be discarded as they do not reproduce SN 2011fe well near maximum light. 5 Direct (head-on) WD collision models (e.g., Rosswog et al 2009;van Rossum et al 2016;Papish & Perets 2016) predict isotope ratios inconsistent with observations (Papish & Perets 2016) which is supported by the non-detection of bimodal nebularphase emission profiles (e.g., Dong et al 2015;Vallely et al 2020). Similarly, graviationally-confined detonations (grav.…”
Section: Discussionmentioning
confidence: 95%
“…Some explosion models can be discarded as they do not reproduce SN 2011fe well near maximum light. 5 Direct (head-on) WD collision models (e.g., Rosswog et al 2009;van Rossum et al 2016;Papish & Perets 2016) predict isotope ratios inconsistent with observations (Papish & Perets 2016) which is supported by the non-detection of bimodal nebularphase emission profiles (e.g., Dong et al 2015;Vallely et al 2020). Similarly, graviationally-confined detonations (grav.…”
Section: Discussionmentioning
confidence: 95%
“…Shifts of up to ∼3000 km s −1 (both to the blue and to the red) in iron and nickel forbidden emission lines have been identified in spectra at ∼200 days past maximum, indicating relatively large asymmetries in the inner Fe-rich ejecta, and these seem to be correlated with early-time properties ( Figure 5), perhaps suggesting an orientation effect 99,101 . Approximately 15% of SN Ia show signatures of double-peaked nebular emission lines separated by ∼5000 km s −1 , and the fraction rises for subluminous SN Ia 105,106 ; this may result from two explosion sites in a white dwarf collision model.…”
Section: Type Ia Supernovaementioning
confidence: 99%
“…They showed that various uncertainties related to the physical processes and to the initial profiles of the WD are unlikely to resolve the tension with observations, although they can deteriorate the agreement with observations of low-luminosity SNe Ia. While there are some reasonable initial compositions and reaction rate values for which DDM successfully explains the lowluminosity part of the t0 − MNi56 relation, this model may be in conflict with the observed 56 Ni mass-weighted line-of-sight velocity distribution for a large fraction of these events, as measured from nebular spectra (Dong et al 2015(Dong et al , 2018Vallely, et al 2020). Specifically, the 56 Ni velocity distribution is either double-peaked or highly shifted, which so far has not been predicted by the DDM.…”
Section: Summary and Discussionmentioning
confidence: 83%